A simple and non-invasive method for nuclear transformation of intact-walled Chlamydomonas reinhardtii. - Sora Kim; Young-Chul Lee; Dae-Hyun Cho; Hyun Uk Lee; Yun Suk Huh; Geun-Joong Kim; Hee-Sik Kim (PLoS ONE)
Genetic engineering in microalgae is gaining attraction but nuclear transformation methods available so far are either inefficient or require special equipment. In this study, we employ positively charged nanoparticles, 3-aminopropyl-functionalized magnesium phyllosilicate (aminoclay, approximate unit cell composition of [H2N(CH2)3]8Si8Mg6O12(OH)4), for nuclear transformation into eukaryotic microalgae. TEM and EDX analysis of the process of transformation reveals that aminoclay coats negatively-charged DNA biomolecules and forms a self-assembled hybrid nanostructure. Subsequently, when this nanostructure is mixed with microalgal cells and plated onto selective agar plates with high friction force, cell wall is disrupted facilitating delivery of plasmid DNA into the cell and ultimately to the nucleus. This method is not only simple, inexpensive, and non-toxic to cells but also provides efficient transformation (5.03×10(2) transformants/µg DNA), second only to electroporation which needs advanced instrumentation. We present optimized parameters for efficient transformation including pre-treatment, friction force, concentration of foreign DNA/aminoclay, and plasticity of agar plates. It is also confirmed the successful integration and stable expression of foreign gene in Chlamydomonas reinhardtii through molecular methods.